English in urban classrooms : a multimodal perspective on teaching and learning - Kress, Gunther R. (RoutledgeFalmer, 2005)
Those involved with education and the teaching of English will find this book fascinating account of teaching and learning in urban classrooms, whilst policy shapers, linguists and anyone with an interest in semiotics and multimodality will find.